DAMPAK KEBIJAKAN PENINGKATAN TARAF HIDUP MASYARAKAT DI KEPULAUAN NAIN KABUPATEN MINAHASA UTARA - AMIRI, RISMA SEPTARI; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2017)
Abstract: This research aims to explain the impact of government policy in improving living standard of people in the NainIslands of North Minahasa Regency, in order to improve the welfare of the people. This research uses descriptive methodof qualitative approach, and data collection technique done by observation, interview technique and documentation.Number of informants is 12 (twelve) persons. This research focuses on government policy in the field of entrepreneurship.The analytical techniques used are qualitative analysis models of interactive models from Miles and Huberman. The resultsshowed that the Impact of Government Policy In Improving the Living Standard of People in the Nain Islands NorthMinahasa Regency especially in the field of entrepreneur has not give a significant impact on the community in Nain Island.This is mainly, because the aid programs that are given still pay attention to the relationship of friendship and the nonfunctioningof inter-governmental coordination with the community, the government also does not play an active role inoverseeing the implementation of the community program and the lack of public interest in contributing in the field ofentrepreneurship by the limitations in skillsKeyword : Impact of the Policy, Living Standard, The Peoples